Morphometric analysis of the mental foramen in a Turkish population based on multi-slice computed tomography - Ahmet Ercan Sekerci; Halil Sahman; Yildiray Sisman; Yusuf Aksu (Wolters Kluwer Medknow Publications, 2013)
Purpose : The aim of this study was to determine the location, orientation, shape, appearance, and area of the mental foramen (MF), as seen on CT images, and to compare our findings with international values. Materials and Methods : CT records were randomly selected from the collection of 550 Turkish patients and were evaluated morphometric analysis of the MF. Results : The most common anterior-posterior position of the MF was bilaterally symmetrical and located on the same vertical line with the long axis of the lower second premolar. The majority of foramina were round in shape, and the most frequent appearance was the continuous type. The most frequent (76%) superior-inferior position was situated below the level of the apices of mandibular premolar roots. Conclusions : The results of this study may assist surgeons to localize important maxillofacial neurovascular bundles passing through the MF in avoiding complication from local anesthetic, surgical, and other invasive procedures.